A coding scheme for request for confirmation sequences across languages - König Katharina; Pfeiffer Martin; Weber Kathrin (Open Linguistics)
This article is part of a special issue on cross-linguistic analyses of request for confirmation (RfC) sequences in ten languages. It presents the coding scheme that forms the basis of the comparative study of RfCs in mundane conversation. First, we outline the criteria applied to ensure comparability of data and describe the procedures for building a collection of 200 RfC sequences for each language. We then introduce the coding categories for the RfC turn and the subsequent response. The article also reports on the methods for testing and securing inter-coder reliability in our cross-linguistic project.